When Do the Stigmatized Make Attributions to Discrimination Occurring to the Self and Others? The Roles of Self-Presentation and Need for Control . [article] . - Sechrist, Gretchen B.
Two experiments examined how the goals of self-presentation and maintenance of control over one's outcomes influence women's tendencies to make or to avoid making attributions to discrimination. Demonstrating the importance of self-presentational goals. Experiment 1 showed that the targets of discrimination were just as likely as similar others to make attributions to discriminations under private reporting conditions, but they were significantly less likely to do so under public reporting conditions. This experiment also provided initial evidence that need for personal control increases discrimination attributions. Experiment 2 demonstrated that targets' minimization of discrimination, observed in public reporting conditions, was eliminated when the need to reassert personal control was induced. Both experiments also demonstrated that failing to view events as discrimination has negative psychological costs. -- (from the author)